Desipramine treatment in normal subjects. Effects on neuroendocrine responses to tryptophan and on platelet serotonin (5-HT)-related receptors. - Cowen, P; Geaney, D; Schächter, M; Green, A; Elliott, J (1986)
Normal subjects took the tricyclic antidepressant, desipramine hydrochloride, for 16 days. Following treatment there was an increase in the number of specific binding sites on the platelet for both tritiated imipramine and tritiated LSD, the latter site probably representing a platelet serotonin (5-HT) receptor. During desipramine treatment the prolactin response to tryptophan (L-tryptophan) was enhanced, and this enhancement correlated with the increase in platelet LSD binding. The results confirm previous observations that desipramine administration increases certain 5-HT-mediated neuroendocrine responses. Our findings further indicate that desipramine may alter both 5-HT uptake and 5-HT receptor sensitivity, and suggest that the platelet LSD receptor may in certain conditions provide a useful model of 5-HT receptors in the brain.